Price Trends of Firewood in Haryana - Mathur, R. S.; Sagar, S. R.; Mahendra, A. K. (Indian Forester, 1984)
The main object of the study was to find out the statistical significance of price and its trends for firewood in Haryana. It is observed that average prices of firewood are higher in Haryana in comparison to other states and the rate of increase in prices of firewood in Haryana in 1982 over 1981 is not significant. The species Kikkar got the highest prices in the years 1981 and 1982. Suggestion has been made to blend fuel conservation with tree planting for firewood with new technologies as this may only moderate the rising trend of prices.